Reflections on local government development in Nigeria 1950-75 - Orewa, G. Oka. (Topo, Badagry, Lagos : Administrative Staff College of Nigeria, 1991)
This book bring into focus some of the highlights of local government development in Nigeria during the first twenty five years of the country existence. It also serve as a textbook for the education of the Nigerian students on issues patterning to local government development in Nigeria.
First series statement from jacket.
Includes bibliographical references (p. 213-217).
usc 13/6/17
Loans
Keywords: Local government